I've got to be independent': views of older people on recovery following road traffic injury in New South Wales, Australia - Katherine Brown; Ian D. Cameron; Lisa Keay; Ha Nguyen; Lisa Dillon; Jagnoor Jagnoor; Rebecca Ivers (BMC, 2020)
Abstract Background Mild to moderate road traffic injury (RTI) in people of working age is associated with limited recovery. Less is known about RTI recovery in older age. This study explored the perspectives and factors associated with recovery and health-related quality of life following mild to moderate RTI in older age in New South Wales, Australia. Methods A qualitative study using content analysis was undertaken. Participants aged 65 or more years were purposively selected from a larger inception cohort study of health outcomes following mild to moderate RTI conducted in New South Wales, Australia. Semi-structured interviews were undertaken at approximately 12 or 24 months post-injury. Content analysis was used to code and analyse the data, with methodological rigour obtained by double-coding and discussing findings to reach consensus. Results were reported using the consolidated criteria for reporting qualitative research (COREQ). Results Nineteen participants were invited to participate in the study of which 12 completed interviews. Data saturation was reached at the twelfth interview. Recovery experiences were diverse. Five main themes were identified: recovery is regaining independence; injury and disability in older age; the burden of non-obvious disability; the importance of support; and positive personal approaches. Key facilitators of recovery were: regaining independence; support from family and friends; and positive personal approaches. Key barriers were: threats to independence; passive coping behaviours; non-obvious disabilities (chronic pain, psychological impacts); and reluctance to raise ongoing issues with General Practitioners. Threats to independence, especially not driving and self-care, appeared to have a more profound effect on recovery than physical functioning. Conclusion Older people view injury as a threat to independent functioning. This is somewhat different to what younger people report. Regaining independence is key to older people's recovery and health-related quality of life following RTI, and should be a key consideration for health professionals, services and supports working with this unique cohort. Greater efforts to help older people regain their independence following RTI are needed and can be facilitated by health professionals and appropriate service provision. Trial registration Australia New Zealand clinical trial registry identification number ACTRN12613000889752 .